Mencermati Inklusivisme Agama Nurcholish Madjid - Maria Ulfa (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2013)
The Inclusive theology term is well known in Religious Plurality Discourse. Generally, it can be expressed as a view which sees the truth in other religion although that one still embracing his religion. Inclusive Theology, has been popularized by One of Modern Scholar; Nurcholish Madjid (Cak Nur), as an alternative of violence and religion conflict which in the view of the modernist has reduced the meaning of religion as the claim of salvation. Whereas this theology hasn’t been a solution but new problem caused reduction of the meaning and Islam identity as a Din. As an example is shifting meaning of Islam, from ‘organized religion’ become ‘submission’ is one of big mistakes caused this theology. This work supposed to criticize this concept of Inclusive Theology derived by Cak Nun.